KAJIAN PENYIMPANAN DINGIN TERHADAP MUTU BUNGA POTONG KRISAN - Satriani Stelma Walangitan; Ireine A. Londong STP. MP.; Dr. Ir. Lady Lengkey MSi. (COCOS, 2017)
ABSTRACT The aims of this study is to determine the shelf life and quality change i.e the wilting percentage of  chrysanthemum cut flowers, weight loss, changes in the diameter of the bud and color changes of the flower. This research use descriptive method. Before placing in the refrigerator pre-cooling has been done by dipping the flower stems into 3°C of ice water and held at the average temperature of 7,35°C. The results showed that the longest vase life of chrysanthemum cut flower is 41 days. The wilting reached 100% on 41th day. The average of weight loss percentage is 18,69%. The average of diameter change of flower buds reached the maximum on the 37th day. The color of petals change from white to brown.   Keywords: Pre-cooling, chrysanthemum cut flower, cold storage